Silencing the Odorant Binding Protein RferOBP1768 Reduces the Strong Preference of Palm Weevil for the Major Aggregation Pheromone Compound Ferrugineol - Antony, Binu; Johny, Jibin; Aldosari, Saleh A. (Frontiers in Physiology, 2018)
In insects, perception of the environment – food, mates and prey – is mainly guided by chemical signals. The dynamic process of signal perception involves transport to odorant receptors (ORs) by soluble secretory proteins, odorant binding proteins (OBPs), which form the first stage in the process of olfactory recognition and are analogous to lipocalin family proteins in vertebrates. Although OBPs involved in the transport of pheromones to ORs have been functionally identified in insects, there is to date no report for Coleoptera. Furthermore, there is a lack of information on olfactory perception and the molecular mechanism by which OBPs participate in the transport of aggregation pheromones. We focus on the red palm weevil (RPW) Rhynchophorus ferrugineus, the most devastating quarantine pest of palm trees worldwide. In this work, we constructed libraries of all OBPs and selected antenna-specific and highly expressed OBPs for silencing through RNA interference. Aggregation pheromone compounds, 4-methyl-5-nonanol (ferrugineol) and 4-methyl-5-nonanone (ferruginone), and a kairomone, ethyl acetate, were then sequentially presented to individual RPWs. The results showed that antenna-specific RferOBP1768 aids in the capture and transport of ferrugineol to ORs. Silencing of RferOBP1768, which is responsible for pheromone binding, significantly disrupted pheromone communication. Study of odorant perception in palm weevil is important because the availability of literature regarding the nature and role of olfactory signalling in this insect may reveal likely candidates representative of animal olfaction and, more generally, of molecular recognition. Knowledge of OBPs recognizing the specific pheromone ferrugineol will allow for designing biosensors for the detection of this key compound in weevil monitoring in date palm fields.